(untitled) (Discourse of Law and Administration, 2023)
In public discourse, dark skies have long been considered as a common heritage of humanity that is being lost due to uncontrolled, excessive, and harmful artificial light emissions. The purpose of this paper is to identify an international model for the legal protection of dark skies. The qualification of the dark skies as a separate element of legal protection is problematic, because of the impossibility of defining its boundaries and territorial affiliation. However, the dark skies can be treated as a unique element of the cultural, natural (or mixed) landscape, which creates the identity of a site, giving it an outstanding universal value. The normative analysis included: The Convention Concerning the Protection of the World Cultural and Natural Heritage, the European Landscape Convention, and resolutions of international organizations whose mission is to protect dark skies. In addition, the paper considers the source of the human right to dark skies as an inalienable human right, which grows out of the right to a clean environment.